Нуминозното, возвишеното и непријатно непознатото во теоријата за светото на Рудолф Ото - Тодоровска, Марија (Филозофско друштво на Македонија, 2015)
The text briefly outlines the components of the numinous in Otto’s theory (mysterium tremendum and mysterium fascinans), underlying the feeling of the sacred for the religious human being as of something pertaining to an ontological level far removed from the usual, quotidian, profane one, as something completely different, or wholly other. The problem of ineffability of the sacred experience is shown, as well as the modality of “grasping” it only through analogies, metaphors and similes. This is compared to the feeling of the sublime as an aesthetic experience, and ran through the ideas of some of the main thinkers in the field. The concept of the uncanny (unheimlich) as a profane equivalent of the feeling of the wholly other is then approached, both on its own standing, as well as compared to the comprehension of the sublime.
Keywords: numinous, sublime, uncanny, wholly other, religious (experience)